Persepsi Orang Tua Suku Bajo terhadap Pendidikan Anak-Anak: Suatu Kajian Inovatif - Ririk, Ririk; Mokodompit, Multi; Puspita Sari, Yulinda (Journal of Leadership, Management and Policy in Education, 2023)
This study aims to describe and analyze the perceptions of Bajo ethnic parents towards their children’s education. The type of research used is descriptive qualitative research. The methods used in this study are observation, and interviews. The informants in this study were parents of the Bajo tribe who had school-age children. Data were analyzed using data reduction, data presentation, and drawing conclusions. The results of the study show that parents of the Bajo tribe in Saponda have a strong understanding of importance of education for their children, however they face a number of obstacles in providing a good education, including economic limitations, resources, and inadequate educational facilities and infrastructure. Besides that, this research reveals that there are high expectations of Bajo tribal parents for their children’s education. They hope that their children will get better opportunities in terms of access to education. In a limited cultural and environmental context, social and government support is also very much needed by the Bajo community in Saponda village. Support in the form of financial assistance, as well as educational programs and policies that pay attention to their needs, it is hoped that this will increase the participation of Bajo tribal parents in Saponda in their children’s education.